Surface functionalization of magnetic micro-robots for Removal of Nickel, Lithium and Chromium from wastewater (2022)
This paper presents the feasibility of heavy metal (Ni, Li, Cr) polluted wastewater treatment with functionalized micro-robots. A cross like design of magnetic micro-robots, with suggested material as aluminum (Al), where ensembled and functionalized. The type of functionalization was APTES and Lacasse, the last one was tested under and indirect enzyme activity test. Simulation of polluted wastewater with Ni, Cr and Li, at four different concentrations, was tested with micro-robots for five hours. Additional test was carried out for Cadmium (Cd) and Lead (Pb) as contaminants for eight hours. Results show no variation in heavy metal removal, after ANOVA variance analysis was carried out.